Recent Advances in Enzymes for the Bioremediation of Pollutants. (22nd June 2021) - Mousavi, Seyyed Mojtaba; Hashemi, Seyyed Alireza; Iman Moezzi, Seyed Mohammad; Ravan, Navid; Gholami, Ahmad; Lai, Chin Wei; Chiang, Wei-Hung; Omidifar, Navid; Yousefi, Khadije; Behbudi, Gity
Abstract : Nowadays, pollution of the environment is a huge problem for humans and other organisms' health. Conventional methods of pollutant removal like membrane filtration or ion exchange are not efficient enough to lower the number of pollutants to standard levels. Biological methods, because of their higher efficiency and biocompatibility, are preferred for the remediation of pollutants. These cost-effective and environment-friendly methods of reducing pollutants are called bioremediation. In bioremediation methods, enzymes play the most crucial role. Enzymes can remedy different types of organic and inorganic pollutants, including PAHs, azo dyes, polymers, organocyanides, lead, chromium, and mercury. Different enzymes isolated from various species have been used for the bioremediation of pollutants. Discovering new enzymes and new subtypes with specific physicochemical characteristics would be a promising way to find more efficient and cost-effective tools for the remediation of pollutants.